Abundance of shorebirds (Charadriiformes: Scolopacidae) and its relationship with water temperature in a wetland in Peru (2013-2019): Community aspects of Charadriiformes: Scolopacidae and its relationship with thermal environmental parameters - Podestá, Jorge; Barona, Daniel (Revista de Biología Tropical, 2021)
Introduction: Scolopacidae family (Order: Charadriiformes) is one of the most abundant families found in coastal wetlands. La Arenilla coastal wetland has a historical record of 20 scolopacid species; climatic events could affect the distribution and migration of the several species of this taxonomic family, reducing their species richness and abundance. Objective: The aim of the present study was to determine the relationship between richness and abundance of the species belonging to the Scolopacidae family and both Sea Surface Temperature (SST) and the coastal El Niño index (ICEN) in La Arenilla Coastal Wetland, La Punta, Callao. Methods: Sampling were carried out twice a month, between January 2013 and January 2019 using the Total Count Method in order to determine species abundance (N = 292). A Spearman correlation analysis between abundance, species richness, SST and ICEN was performed, and beta diversity was calculated through the Whittaker index (βw) to analyze both the annual turnover for each season and the seasonal turnover within each year. Results: Two significant correlations were obtained: between SST and abundance and between ICEN and species richness. On the other hand, the ANOSIM test showed seasonal differences in abundance, and the SIMPER test showed that the greatest difference in abundance between seasons was between autumn and spring (Bray-Curtis dissimilarity = 81.57 %), and the minimum difference between winter and spring (Bray-Curtis dissimilarity = 49.86 %). Conclusions: The ecological dynamics of scolopacid communities in La Arenilla coastal wetland face important changes according to the variations in the environmental thermal parameters related to climate change.